Analisa Infrastruktur Jaringan Wireless dan Local Area Network (WLAN) Meggunakan Wireshark Serta Metode Penetration Testing Kali Linux - Tri Yusnanto; Muhammad Abdul Muin; Sugeng Wahyudiono (Journal on Education, 2022)
Computer networks and the internet play an important role for the smooth running of various fields of work. One example of information and communication technology is the Wireless Local Area Network (WLAN) or also called wireless local network technology. The method used in this research is the Penetration Testing method, with the intention of analyzing the Wireless Network computer security system in the STMIK Bina Patria Laboratory. Testing is carried out with several activities, including identifying and exploiting vulnerabilities in computer network security. In analyzing the security of the WLAN network, it is carried out using the Penetration Testing method where a form of attack on the network is simulated, one of the operating systems that has the right specifications in this regard is Kali Linux. Wireless network is a network that is widely used in institutions and public places. Even though it has a security system, wireless networks can still be attacked by attackers.